Isthmic spondylolisthesis combined with schwannoma occurring at the same vertebral level: a case report and literature review - Niu, Renrui; Zhao, Jianhui; Li, Chaoyuan; Guo, Fengshuo; Duan, Yuchi; Luo, Wenqi; Gu, Rui (Frontiers in Surgery, 2025)
BackgroundThe occurrence of schwannomas at the level of isthmic spondylolisthesis has not yet been reported. Preoperative identification of the responsible lesion and a rational surgical plan are essential for successful surgery.Case presentationWe report the case of a 56-year-old woman who presented with a six-year history of low back pain and a three-year history of radiating pain in the left lower extremity. Physical examination revealed signs of left L5 root compression. Computed tomography revealed left L5–S1 intervertebral foramen stenosis with an isthmic fracture. Unexpectedly, magnetic resonance imaging (MRI) showed an abnormal 12 mm*11 mm*21 mm intradural mass with inhomogeneous contrast enhancement at the level of the spondylolisthesis. Isthmic spondylolisthesis and schwannoma were suspected. Based on the imaging and physical findings, we inferred that the lower-extremity pain was primarily caused by lumbar spondylolisthesis. Under general anesthesia, the patient underwent posterior lumbar interbody fusion of L5–S1 and intradural total tumorectomy. Histopathological examination of the surgical specimen revealed a schwannoma. The patient's symptoms resolved postoperatively, and intervertebral fusion was satisfactory at the 12-month follow-up.ConclusionThis case demonstrates the difficulty of determining the responsible lesion, highlighting the importance of meticulous clinical and imaging examinations. Determining the responsible lesion is crucial for diagnosis and treatment.